2007
DOI: 10.1055/s-2007-990240
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Mycoepoxydiene Derivatives from an Endophytic Fungus Phomopsis sp. Isolated from Hydnocarpus anthelminthicus

Abstract: Mycoepoxydiene ( 1) and derivatives, deacetylmycoepoxydiene ( 2) and 2,3-dihydromycoepoxydiene ( 3), were isolated from a broth extract of the endophytic fungus, phomopsis sp., which was isolated from a Thai medicinal plant, Hydnocarpus anthelminthicus. Compounds 1 and 2 exhibited potent cytotoxic activity, while a dihydro derivative 3 was inactive. The present work suggests that the alpha,beta-unsaturated lactone moiety in mycoepoxydienes might be responsible for the cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 8 publications
3
28
0
Order By: Relevance
“…Primers ITS5 (GGAAGTAAAAGTCGTAACAAGG) and ITS4 (TCCTCCGCTTATTGATATGC) [24] were used to amplify the ITS1-5.8S-ITS2 region from the extracted DNA, and the PCR product was subjected to DNA sequencing as previously described. [25] A BLAST 2.2.22 + search [26] through the GenBank database for DNA sequence similarity suggested that the CTOM11 strain is a fungus in the genus Curvularia. However, the ITS1-5.8S-ITS2 sequences of reference fungal type strains were not available in the GenBank database, which made reliable species assignment for the CTOM11 strain not possible by this method.…”
mentioning
confidence: 99%
“…Primers ITS5 (GGAAGTAAAAGTCGTAACAAGG) and ITS4 (TCCTCCGCTTATTGATATGC) [24] were used to amplify the ITS1-5.8S-ITS2 region from the extracted DNA, and the PCR product was subjected to DNA sequencing as previously described. [25] A BLAST 2.2.22 + search [26] through the GenBank database for DNA sequence similarity suggested that the CTOM11 strain is a fungus in the genus Curvularia. However, the ITS1-5.8S-ITS2 sequences of reference fungal type strains were not available in the GenBank database, which made reliable species assignment for the CTOM11 strain not possible by this method.…”
mentioning
confidence: 99%
“…Phomopsis, Penicillium and Xylaria were the fungal genera that presented the highest antibacterial activity. Fungi of these genera are well known in the literature for their biological activities and several studies prove their potential as producers of biologically active secondary metabolites (Kobayashi et al, 2003;Prachya et al, 2007;Rukachaisirikul et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hant25 was obtained from our previous study [9]. Inoculum was prepared by growing Hant25 on potato dextrose agar (PDA) plates at 25°C for 7 days.…”
Section: Microorganism and Inoculum Preparationmentioning
confidence: 99%
“…With Phomopsis sp. Hant25, no mycoepoxydiene was detectable in malt Czapek broth shake-Xask culture but 26 mg l ¡1 was obtained from static culture [9] where the fungus grew at the medium surface. We hypothesized that surface culture enhances mycoepoxydiene production in the Hant25 fungus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation